Design and Development of a Digital Platform for Soil Health Monitoring and Management - Patil, Mukund; Burry, Sukanya; Katakamsetti, Nagendra; Choudhari, Pushpajeet L.; Perumal, Cuba; Gogumalla, Pranuthi; Rozario, Gilbert; Shaik, Jameeruddin; Rupavatharam, Srikanth (2025)
Soil health information is essential for improving crop productivity, fertilizer use efficiency, and sustainable land management. However, soil data are often scattered, inconsistently collected, and difficult to translate into practical advisories for farmers and extension systems. This working report presents the design and implementation of an integrated digital platform for soil data management, digital soil mapping, and decision support. The platform supports end-to-end workflows, including farmer and farm registration, geo-referenced soil sample collection, laboratory data entry, quality control, spatial analysis, and generation of soil fertility maps and fertilizer recommendations. The system integrates standardized master data for locations, crops, seasons, and management practices, enabling consistent referencing across modules. A digital soil mapping engine is embedded within the platform to generate district-level soil nutrient maps using available soil samples, subject to minimum data and spatial distribution requirements. The platform also includes dashboards and visualization tools to explore soil fertility status and summary statistics, supporting both field-level decisions and higher-level planning. Offline data entry through mobile applications allows soil samples to be recorded in areas with limited connectivity, with synchronization once internet access is available. The report discusses key limitations related to data quality, sampling density, computational requirements, connectivity constraints, institutional readiness, and model interpretability, along with practical mitigation strategies. Overall, the platform demonstrates a scalable and interoperable approach to converting soil test data into actionable digital outputs. The proposed system can support soil test–based nutrient management, strengthen extension services, and contribute to data-driven agricultural decision making. Future work will focus on improving model transparency, expanding spatial coverage, and embedding the platform within national digital agriculture initiatives for long-term sustainability.